Structure, absolute configuration, and conformational study of resorcylic acid derivatives and related congeners from the fungus Penicillium brocae1. Issue 50 (4th June 2015) - Zhang, Peng; Meng, Ling-Hong; Mándi, Attila; Li, Xiao-Ming; Kurtán, Tibor; Wang, Bin-Gui
<x xml:space="preserve">Abstract</x> A new resorcylic acid derivative (4) and five new loop-opened resorcylic acid-related congeners (5–9), were identified from the marine mangrove-derived endophyte Penicillium brocae MA-192. All compounds were evaluated for the antioxidant activity against DPPH and ABTS radicals.